Paracetamol induced fixed drug eruptions: case report - Raipurkar, Swati V.; Patel, Poonam; Mucchal, Vijay; Khurana, Randhir; Wadagbalkar, Prashant (International Journal of Contemporary Pediatrics, 2017)
Paracetamol is widely used by physician and people thinking that it is very safe drug. But it must be remembered that every drug can cause adverse reaction. Cutaneous drug eruptions are one of the most common types of adverse reaction to drug therapy, with an overall incidence rate of 2-3% in hospitalised patients. Non-Steroidal Anti-Inflammatory Drugs (NSAIDs), antibiotics and antiepileptics, have drug eruption rates approaching 1–5%. Here we have noted a case of 2 year child with fixed drug eruption due to paracetamol which developed a few hours later after intake of paracetamol syrup.